Análise da compra institucional da agricultura familiar no PNAE no município de Santa Helena - PR - Souza, Camila Orlando de (2025)
The National School Feeding Program (PNAE) is a public policy initiative designed to ensure adequate nutrition for students in basic education, while promoting food and nutritional security, fostering healthy dietary practices, and valuing local food culture. Legislation mandates that a minimum of 30% of the financial resources transferred be allocated to the procurement of foodstuffs from family farming, thereby reinforcing local economies and sustainable agriculture. This study aims to examine the process functioning of the PNAE in the municipality of Santa Helena, Paraná, over the period from 2009 to 2022, with emphasis on the participation of family farmers and to identify the primary seeks and challenges and opportunities encountered. A descriptive and bibliographic research design was employed, incorporating both qualitative and quantitative methodological approaches. Data collection involved the administration of semi-structured interviews with the municipal nutritionist responsible for overseeing the PNAE, as well as with family farmers who supply food to the program. The research instrument comprised both closed-ended and open-ended questions, facilitating the collection of in-depth qualitative data. The study received approval from the Research Ethics Committee. Collected data were systematized in spreadsheets and analyzed through qualitative content analysis based on the interview transcripts. Findings suggest an increasing level of integration between local government structures and family farming stakeholders, with full compliance regarding the allocation of funds to family agriculture. Menu planning is carried out by the municipal nutritionist, based on the dual criteria of school nutritional requirements and the seasonal availability of local produce. The farmers’ association plays a pivotal role in maintaining the quality of food items supplied and coordinates substitutions when necessary. Although family farming in the region exhibits a certain degree of diversity, the range of products incorporated into school meals remains limited. This underscores the need for public policies aimed at incentivizing organic agriculture and agroecological production systems, with the goal of enhancing the sustainability of the program. The study further emphasizes the program’s direct contribution to the achievement of Sustainable Development Goals (SDGs) 2, 3 , 4, 10 and 12, alongside indirect contributions to SDGs 5, 13 and 15. In conclusion, the PNAE emerges as a strategic public policy instrument for promoting healthy eating, inclusive rural development, and sustainable territorial development in local contexts.